2022
DOI: 10.3389/fmed.2022.911737
|View full text |Cite
|
Sign up to set email alerts
|

Using random forest algorithm for glomerular and tubular injury diagnosis

Abstract: ObjectivesChronic kidney disease (CKD) is a common chronic condition with high incidence and insidious onset. Glomerular injury (GI) and tubular injury (TI) represent early manifestations of CKD and could indicate the risk of its development. In this study, we aimed to classify GI and TI using three machine learning algorithms to promote their early diagnosis and slow the progression of CKD.MethodsDemographic information, physical examination, blood, and morning urine samples were first collected from 13,550 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Amid the ageing population in China, the prevalence of hypertension, diabetes mellitus and other chronic diseases has risen sharply, especially in rural areas of China subjected to relatively backward medical conditions and less access to regular medical examination accompanied by poor health awareness 41 , 42 . The elderly often comes with HHcy and other several conditions, exacerbating the possibility of cardiovascular and cerebrovascular development, becoming the “silent killer” of health 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Amid the ageing population in China, the prevalence of hypertension, diabetes mellitus and other chronic diseases has risen sharply, especially in rural areas of China subjected to relatively backward medical conditions and less access to regular medical examination accompanied by poor health awareness 41 , 42 . The elderly often comes with HHcy and other several conditions, exacerbating the possibility of cardiovascular and cerebrovascular development, becoming the “silent killer” of health 43 .…”
Section: Discussionmentioning
confidence: 99%
“…In our previous work ( 32 ), we also employed LR, RF and Naive Bayes algorithms to make a classification of glomerular injury and tubular injury with the same population. The results suggested that RF performs best and could be employed as a novel auxiliary diagnostic approach for glomerular injury and tubular injury.…”
Section: Discussionmentioning
confidence: 99%
“…Another previous study constructed 3 algorithms, namely RF, plain Bayesian, and LR, to classify glomerular and tubular injury and found that RF showed the best performance in terms of accuracy, sensitivity, and specificity. These findings suggest that RF can facilitate early diagnosis of glomerular and tubular injury to mitigate CKD progression [ 23 ]. Therefore, previous studies on the viability of RF models have reported inconsistent conclusions due to differences in research perspectives and subjects.…”
Section: Introductionmentioning
confidence: 99%